PERSEPSI PEMANGKU KEPENTINGAN MENGENAI POTENSI PARIWISATA SEBAGAI PEMEREKAN KOTA CIREBON - Mihardja, Eli Jamilah; Rudianto, Dudi (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2018)
In an effort to form city branding, the first step is a survey of perceptions and expectations about a region either from the local community itself as well as outside parties who have relevance to the area. Cirebon has great tourism potential to be developed as citybranding, but still unknown chances. Therefore, this research is conducted on tourist visitors as one of stakeholder to know their perception about Cirebon tourism potential to be a city brand. As a result, visitor perception is positive so policy makers can develop it as a strategy to form citybranding of Cirebon Municipal City. To cite this article (7th APA style): Mihardja, E. J. & Rudianto, D. (2018). Persepsi Pemangku Kepentingan Mengenai Potensi Pariwisata Sebagai Pemerekan Kota Cirebon [Stakeholder’s Perception about Citybranding Potentials of Cirebon]. Journal Communication Spectrum, 8(1), 56-71. http://dx.doi.org/10.36782/jcs.v8i1.1812